2018
DOI: 10.1016/j.bj.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment mediated by suppression of autophagic flux drives liver malignancy

Abstract: The physiological role of autophagy in the catabolic process of the body involves protein synthesis and degradation in homeostasis under normal and stressed conditions. In hepatocellular carcinoma (HCC), the role of tumor microenvironment (TME) has been concerned as the main issue in fighting against this deadly malignancy. During the last decade, the crosstalk between tumor cells and their TME in HCC extensively accumulated. However, a deeper knowledge for the actual function of autophagy in this interconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The mTOR-TSC2 pathway, a key negative regulator of autophagy, is crucial for macrophage polarization since its activation leads to M2 phenotype. It was recently shown that the coagulants tissue factor (TF) and factor VII (FVII) produced in tumor microenvironment, are implicated in HCC growth promotion by suppression of autophagy mediated through mTOR activation and Atg7[ 551 ].…”
Section: Hccmentioning
confidence: 99%
“…The mTOR-TSC2 pathway, a key negative regulator of autophagy, is crucial for macrophage polarization since its activation leads to M2 phenotype. It was recently shown that the coagulants tissue factor (TF) and factor VII (FVII) produced in tumor microenvironment, are implicated in HCC growth promotion by suppression of autophagy mediated through mTOR activation and Atg7[ 551 ].…”
Section: Hccmentioning
confidence: 99%
“…Furthermore, this association may not be solely related to TF expression in the primary tumors as results have now shown that circulating microparticles carrying TF are 16- to 26-fold higher in pancreatic cancer patients with thrombosis when compared to healthy controls ( 183 ). There is emerging evidence that there is an involvement of the autophagy cascade in the mechanism controlling and promoting cancer progression and cancer-related thrombosis ( 23 , 184 ). Proteins of the autophagy pathway are associated with cancer cell chemotherapy and radiation sensitivity through the alleviation of cellular stress and the dampening of apoptosis.…”
Section: Coagulation and Autophagy Cascade In Cancer Cellsmentioning
confidence: 99%
“…Additionally, downregulation of autophagy is associated with enhanced secretion of inflammatory mediators, such as IL-1β, TNF-α, and Monocyte Chemoattractant Protein-1 (MCP-1) ( 24 ). The aforementioned data suggest that activation of PAR2 by TF-FVII-Xa suppresses the autophagic pathway in a PI3K/AKT/mTOR-dependent manner ( 184 ), contributing to the generation of an inflammatory microenvironment that may lead to increased cancer cell migration and invasiveness. In this way, PAR signaling could directly promote tumor growth.…”
Section: Coagulation and Autophagy Cascade In Cancer Cellsmentioning
confidence: 99%
“…In this short review, Chen et al. [27] discuss how the inhibition of autophagy drives the progression of liver cancer and describe the molecular mechanisms in the tumor microenvironment underpinning this effect.…”
Section: Also In This Issuementioning
confidence: 99%